Use of Intravascular Ultrasound and Extravascular Ultrasound During Endovascular Therapy - Tatsuya Nakama; Fadi Saab; Mahmoud Abdelghany; Imraan Ansaarie; Mario D'Oria; Grigorios Korosoglou; Masahiko Fujihara; Pradeep Nair; Bob Tahara; Sameh Sayfo; Zola N'Dandu (Journal of Critical Limb Ischemia, 2026)
During endovascular therapy (EVT) for peripheral artery disease (PAD), intravascular ultrasound (IVUS) and extravascular ultrasound (EVUS) can provide information that is not available from angiography alone, including accurate vessel sizing, plaque morphology, calcification distribution, and assessment of dissections or stent expansion. By complementing angiography, these imaging modalities may improve procedural precision and support appropriate treatment strategies. This narrative review summarizes the practical applications and limitations of IVUS and EVUS in contemporary EVT for PAD.